2015
DOI: 10.1080/10548408.2014.998359
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle segmentation of tourists seeking nature-based experiences: the role of cultural values and travel motives

Abstract: The increasing globalization of markets and the criticality of reaching the right lifestyle segments make the relationship between personal motives and cultural values an important area for academic research and managerial practice. The authors seek to provide an understanding of this relationship in a tourism context, specifically in terms of the links between travel motivations and a set of cultural values -materialism, uncertainty avoidance, horizontal and vertical individualism, and horizontal and vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
39
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 113 publications
(168 reference statements)
16
39
0
2
Order By: Relevance
“…This study considered travel motivations, demographics, travel behaviors, information channels, and payment preferences of Chinese tourists to Pacific SIDS. Building on the concept of cultural determinism adopted by Steigerwald (2005) and Cohen (2011), travel motivation is an internal driving force that critically determines an individual's preferred lifestyle and travel behaviors (Iversen et al, 2016;Zhou & Huang, 2016). where Asian visitors who are interested in exploring different cultures and experiencing the local way of life while trying to shop even in local markets, store or malls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study considered travel motivations, demographics, travel behaviors, information channels, and payment preferences of Chinese tourists to Pacific SIDS. Building on the concept of cultural determinism adopted by Steigerwald (2005) and Cohen (2011), travel motivation is an internal driving force that critically determines an individual's preferred lifestyle and travel behaviors (Iversen et al, 2016;Zhou & Huang, 2016). where Asian visitors who are interested in exploring different cultures and experiencing the local way of life while trying to shop even in local markets, store or malls.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a person's values, attitudes, and orientation are determined by their lifestyle (Cohen, 2011). A recent study by Iversen, Hem, and Mehmetoglu (2016) on nature-based travelers to Norway found that travel motives and cultural values could differ between different lifestyles. This study looks at what attractions and activities would motivate Chinese tourists to visit and participate in travel experiences.…”
Section: Travel Motivationmentioning
confidence: 99%
“…Over time, lifestyle has received increasing attention in the marketing domain for its functions in the prediction, explanation, and reflection of consumer behavior. Lifestyle is also a key factor in market segmentation and strategy development; it can provide rich information about customers compared to sociodemographic variables (Iversen et al, 2016).…”
Section: Editorialmentioning
confidence: 99%
“…Fodness (1994) mentions that motivation is the driving force behind all behaviour, while Crompton and McKay (1997) also indicate that motives are the starting points that launch decision processes. It is, however, important to note that motivation differs from person to person and can be greatly influenced by the type and nature of a destination (Sung, Chang & Sung 2016;Iversen, Hem & Mehmetoglu 2016). Applying a segmentation technique aimed at identifying market segments provides several advantages, including: (1) effectively determining market niches based on similarities, (2) classifying groups of tourists, (3) establishing theories related to tourist groups and (4) testing whether the tourist groups are present in the market (Cross, Belich & Rudelius 2015;Dibb & Simkin 2016;Kotler et al 2015;Mazanec 2015).…”
Section: Market Segmentationmentioning
confidence: 99%